Risk factors for pleural effusion in children with plastic bronchitis caused by pneumonia - Lin, Xiaoliang; Xu, Enhui; Zhang, Tan; Zhu, Qiguo; Zhuang, Deyi (Frontiers in Pediatrics, 2024)
Objective: We aimed to investigate the clinical features of children with plastic bronchitis caused by pneumonia, and assess the risk factors for pleural effusion (PE) in plastic bronchitis. Methods: A retrospective study was conducted on children with plastic bronchitis and hospitalized in Xiamen Children's Hospital from January 2017 to April 2023. Participants were categorized based on the presence of PE. Their clinical manifestations and laboratory findings were analyzed. Results: Sixty-nine children with plastic bronchitis were enrolled: 34 cases (49.27%) in the non-PE group and 35 cases (50.72%) in the PE group. No significant differences were found in sex, age, and etiology between the two groups. Significant differences were found in fever duration, C-reactive protein (CRP), albumin and lactate dehydrogenase (LDH) (p < 0.05). A receiver operating characteristic (ROC) curve analysis showed that the cut-off values for higher risk of PE were CRP > 31.66 mg/L or LDH > 551 U/L. The prediction of PE was performed with the combination of CRP > 31.66 mg/L and LDH > 551 U/L, using multivariate logistic regression analysis. The area under the curve (AUC) for logistic regression was 0.797. Elevated CRP increased the risk of PE (odds ratio [OR] 8.358, 95% confidence interval [CI] 2.179-42.900, p = 0.0042), elevated LDH increased the risk of PE (OR 5.851 [95% CI 1.950-19.350], p = 0.0023). Conclusion: The combined detection of CRP and LDH helps predict the risk of PE in children with plastic bronchitis caused by pneumonia.